2018
DOI: 10.1177/1010539518806809
|View full text |Cite
|
Sign up to set email alerts
|

Older Community Residents Who Participate in Group Activities Have Higher Daily Physical Activity Levels and Lower Medical Costs

Abstract: Participation in a group activity improves levels of activities of daily living and self-rated health in community-dwelling older adults. However, whether the group activity is associated with daily physical activity (PA) levels and medical costs has not yet been explored. The author administered a questionnaire to participants of group activities for community-dwelling older adults. Levels of daily PA were greater in those who participated once a month (n = 1147), twice a month (n = 1432), and 4 times a month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In Japan, the relationship between social participation and each factor in older adults has been investigated. In addition, in previous studies, social participation was associated with better cognitive function [19][20][21][22][23] ; less depressive symptoms [24][25][26][27][28] and psychological distress 29 ) ; more instrumental activities of daily living [30][31][32] ; less functional disability [33][34][35][36][37][38] ; better physical activity [39][40][41] ; better life-space mobility 42 ) ; better mental health 43 ) ; self-related health 44 ) and health-related quality of life 45 ) ; social isolation 46,47 ) ; medical care costs 46,47 ) ; and a lower incidence of dementia 48) , frailty [49][50][51] , and mortality 52) in Japanese older adults (Fig. 1).…”
Section: Fifth Levelmentioning
confidence: 84%
“…In Japan, the relationship between social participation and each factor in older adults has been investigated. In addition, in previous studies, social participation was associated with better cognitive function [19][20][21][22][23] ; less depressive symptoms [24][25][26][27][28] and psychological distress 29 ) ; more instrumental activities of daily living [30][31][32] ; less functional disability [33][34][35][36][37][38] ; better physical activity [39][40][41] ; better life-space mobility 42 ) ; better mental health 43 ) ; self-related health 44 ) and health-related quality of life 45 ) ; social isolation 46,47 ) ; medical care costs 46,47 ) ; and a lower incidence of dementia 48) , frailty [49][50][51] , and mortality 52) in Japanese older adults (Fig. 1).…”
Section: Fifth Levelmentioning
confidence: 84%
“…A growing number of studies have indicated the important role of social engagement in promoting health and reducing the burden of caregiving among older adults (12,13). A study has also suggested that older people who engage in group activities have lower medical costs (14).…”
Section: The Role Of Social Engagement In Coping With Aging In Chinese Populationmentioning
confidence: 99%